Bergenia Genus: Traditional Uses, Phytochemistry and Pharmacology - Bhupendra Koul; Arvind Kumar; Dhananjay Yadav; Jun-O. Jin (Molecules, 2020)
Bergenia (Saxifragaceae) genus is native to central Asia and encompasses 32 known species. Among these, nine are of pharmacological relevance. In the Indian system of traditional medicine (Ayurveda), “Pashanabheda” (stone breaker) is an elite drug formulation obtained from the rhizomes of B. ligulata. Bergenia species also possess several other biological activities like diuretic, antidiabetic, antitussive, insecticidal, anti-inflammatory, antipyretic, anti-bradykinin, antiviral, antibacterial, antimalarial, hepatoprotective, antiulcer, anticancer, antioxidant, antiobesity, and adaptogenic. This review provides explicit information on the traditional uses, phytochemistry, and pharmacological significance of the genus Bergenia. The extant literature concerned was systematically collected from various databases, weblinks, blogs, books, and theses to select 174 references for detailed analysis. To date, 152 chemical constituents have been identified and characterized from the genus Bergenia that belong to the chemical classes of polyphenols, phenolic-glycosides, lactones, quinones, sterols, tannins, terpenes, and others. B. crassifolia alone possesses 104 bioactive compounds. Meticulous pharmacological and phytochemical studies on Bergenia species and its conservation could yield more reliable compounds and products of pharmacological significance for better healthcare.